Optimal control of double pendulum crane using FOPID and genetic algorithm - Elhabib, Mohamed O.; Wahid, Herman; Mohamed, Zaharuddin; Jaafar, Hazriq Izzuan (2024)
Gantry cranes are commonly utilized to transfer huge loads in construction projects as well as essential sectors such as petrochemical and nuclear power. The objective of their operation is to achieve high levels of precision in trolley positioning while simultaneously reducing the amplitudes of sway oscillations. The goal of control approaches is to achieve optimum operational efficiency by maintaining accurate trolley placement while simultaneously meeting safety requirements by reducing sway-induced oscillatory oscillations. To satisfy control objective this paper considered the design of fractional order PID (FOPID) with help of genetic algorithm to compute controller parameters using MATLAB Software. Simulation results showed the controller performance is better than classic PID and also it was capable of providing good response for different payload masses.